Green pre-concentration techniques during pesticide analysis in food samples. Issue 9 (2nd September 2019) - Musarurwa, Herbert; Chimuka, Luke; Tavengwa, Nikita Tawanda
Abstract: The ever-increasing demand for determining pesticides at low concentration levels in different food matrices requires a preliminary step of pre-concentration which is considered a crucial stage. Recently, the parameter of "greenness" during sample pre-concentration of pesticides in food matrices is as important as selectivity in order to avoid using harmful organic solvents during sample preparation. Developing new green pre-concentration techniques is one of the key subjects. Thus, to reduce the impact on the environment during trace analysis of pesticides in food matrices, new developments in pre-concentration have gone in three separate directions: the search for more environmentally friendly solvents, miniaturization and development of solvent-free pre-concentration techniques. Eco-friendly solvents such as supercritical fluids, ionic liquids and natural deep eutectic solvents have been developed for use as extraction solvents during pre-concentration of pesticides in food matrices. Also, miniaturized pre-concentration techniques such as QuEChERS, dispersive liquid–liquid micro-extraction and hollow-fiber liquid-phase micro-extraction have been used during trace analysis of pesticides in food samples as well as solvent-free techniques such as solid-phase micro-extraction and stir bar sorptive extraction. All these developments which are aimed at ensuring that pesticide pre-concentration in different food matrices is green are critically reviewed in this paper.